Bridging the gaps sector to sector and research to policy: linking family planning to urban development. Issue 6 (18th August 2021) - Harpham, Trudy; Smith, Robert; LeGrand, Tom; Cleland, John; Duminy, James; Parnell, Susan; Helzner, Judith F.; Agesa, Gaye; Kamau, Lynette
ABSTRACT: There is growing science and policy interest in multi-sectoral action, but bridging the gap between family planning and urban development is challenging. This paper analyses the experience of integrating these sectors in sub-Saharan Africa via building research capacity. Family-planning researchers were supported to link with urban-development actors, one goal being to generate lessons on the process of getting their research into the policy domain. The urban governance sector's dynamic and complex nature was a particular challenge for family-planning researchers; in future, structured familiarisation with a sector might facilitate multi-sectoral action and better enable researchers to link with the policy world.